Desain Model Kulturaviva sebagai Upaya Penyelamatan Bahasa Terancam Punah - La Ino; Muhamad Chairul Basrun Umanailo; Rasiah Rasiah (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
The phenomenon of language extinction has become a global cultural issue that threatens the sustainability of the identity, traditional knowledge, and social cohesion of the communities that speak them. This study developed and tested a cultural education model, Kulturaviva, to revitalize endangered languages through a culture- and community-based approach. This model integrates linguistic aspects, cultural values, and local traditions in a contextually grounded, participatory learning process. The research design used a User Acceptance Testing (UAT) approach to assess the effectiveness, functionality, and user acceptance of the model, implemented across several communities speaking local languages. The trial results showed a high success rate for the participatory and collaborative approach (82%) and the effectiveness of native speakers in language learning (89%). Cultural activity-based learning showed a moderate success rate (64%), with 36% of participants not achieving the expected targets. 18% of activities required revalidation due to differences in social context and field dynamics. The participant satisfaction rate reached 80%, indicating that the community well received the model. However, improvements are needed in integrating educational technology, accommodating variations in learning methods, and adapting to the local characteristics of each community. Overall, Kulturaviva has proven effective as a cultural education model for saving endangered languages. This approach not only contributes to linguistic preservation but also strengthens cultural identity, fosters language pride, and builds cultural resilience amidst globalization.